Extrahepatic Nonreticuloendothelial Siderosis Is Not Specific to Gestational Alloimmune Liver Disease. (July 2019) - Wu, Hao; Ferguson, William; Castro, Eumenia; Kearney, Debra; Finegold, Milton; Patel, Kalyani
Autopsy reports of 78 stillbirths and early infant deaths (up to age 8 weeks) were reviewed to investigate the prevalence of extrahepatic nonreticuloendothelial siderosis (EHNRS) in the context of neonatal liver failure. Of these, 10 liveborns (12.8%), M:F 3:2, with mean gestational age 37.6 weeks (range: 35–39) and mean age at the time of demise 19.1 days (range: 7–42), showed significant liver injury: infection (n = 7, viral > fungal), congenital malformations (n = 2), and ischemia (n = 1). None had maternal history of gestational alloimmune liver disease (GALD) or previous fetal/neonatal death due to liver failure. Seven of 10 cases (70%) showed EHNRS: pancreas (n = 6), kidneys (n = 4), thyroid and adrenal glands (n = 3), and bronchial glands and heart (n = 2). Iron deposition was most frequent in the pancreas (60%), most diffuse in the kidneys, and seen in at least 2 organs, with pancreas and kidney being the most frequent combination. Hepatic C5b-9 expression was variable (1+ to 4+) except 1 case (100% necrosis). The duration of illness and the mean age at the time of demise tended to be higher in those with EHNRS. In summary, hepatic and EHNRS, with or without C5b-9 expression, are not specific for GALD. Other causes of liver failure should be investigated as clinically and pathologically appropriate.